Label-free observation of morphological alteration of irradiated-urothelial bladder carcinoma cells through digital holographic microscopy - Xiao, Xi; Che, Leiping; Li, Yinjia; Peng, Ran; Wang, Mingqing; Xiao, Wen; Pan, Feng; Wang, Hao (Frontiers in Physics, 2022)
Radiotherapy is an effective treatment for certain patients with muscle-invasive bladder cancer and radio-sensitivity detection plays a vital role during bladder cancer radio treatment because radiotherapy responses have profound influences on a patient’s prognosis. Although several potential biomarkers were investigated to assess the radio-response of bladder cancer, studies on detecting radio-sensitivity based on morphological characteristics of cancer cells at the single-cell level are rare. In fact, morphological parameters are vital characteristics of cells that could provide direct information to infer the physiological statuses of cells and evaluate the response of cells to the external stimulations. In this study, digital holographic microscopy was applied to quantify morphological parameters of bladder cancer cells (HT-1376) at the single-cell level and their alterations after exposure to four different radiation doses, i.e., 0Gy (control), 4Gy, 8Gy, and 12Gy. Based on the reconstructed phase images, four morphological parameters of cells, namely, cell phase volume (CPV), cell projected area (CPA), cell average phase height (CAPH), and cell maximum phase height (CMPH), were quantitatively calculated. The results show that the change rates of CPV, CAPH, and CMPH were increased with the radiation dose rising, while the change rate of CPA was decreased with the radiation dose increasing. Moreover, the change rates of CPV, CPA, CAPH, and CMPH were different between control group and 12Gy treated group. The results demonstrate that morphological characteristics have the potential to be utilized to estimate the radio-sensitivity of bladder cancer cells, and it may provide new perspectives to establishing label-free methods to detect radio-sensitivity and guide radiotherapy in bladder cancer.